2014
DOI: 10.2174/1389201015666140528152946
|View full text |Cite
|
Sign up to set email alerts
|

α-(-)-bisabolol Reduces Pro-inflammatory Cytokine Production and Ameliorates Skin Inflammation

Abstract: α-(-)-bisabolol is a natural monocyclic sesquiterpene present in the essential oil has generated considerable interest in the chemical and pharmaceutical industries and currently in use in various formulations, mainly in cosmetics. This study was undertaken to evaluate its therapeutic profile against skin inflammation using in-vitro, in-vivo and in-silico assays. Lipopolysachharide (LPS) and 12-O-tetradecanoyl-phorbol-13-acetate (TPA)-induced production of proinflammatory cytokines (TNF-α and IL-6) in macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 8 publications
2
53
0
2
Order By: Relevance
“…Also according to Madhavan (1999), alpha-bisabolol was negative in a dermal photosensitization study with guinea pigs and, in addition, a 28-day dermal toxicity study performed through the application of a solution containing 4% of alpha-bisabolol with 87.5% purity on rats showed that the no-observable-adverse-effect level (NOAEL) was equal to 200 mg/kg/day. More recent data show that alpha-bisabolol is not irritant to rabbits when topically administered at 1% over an area of one square inch (Maurya et al, 2014). Based on the evidence described above, and on the values of the ratio between the mass of the membranes per area (around 6 and 5 mg/cm 2 for PCL and Ch-G membranes, respectively), it is possible to assume that even the cumulative dose of 300 mgalphabisabolol/gmembrane administered through the skin would be safe to treat skin lesions.…”
Section: Alpha-bisabolol Release Kineticsmentioning
confidence: 99%
“…Also according to Madhavan (1999), alpha-bisabolol was negative in a dermal photosensitization study with guinea pigs and, in addition, a 28-day dermal toxicity study performed through the application of a solution containing 4% of alpha-bisabolol with 87.5% purity on rats showed that the no-observable-adverse-effect level (NOAEL) was equal to 200 mg/kg/day. More recent data show that alpha-bisabolol is not irritant to rabbits when topically administered at 1% over an area of one square inch (Maurya et al, 2014). Based on the evidence described above, and on the values of the ratio between the mass of the membranes per area (around 6 and 5 mg/cm 2 for PCL and Ch-G membranes, respectively), it is possible to assume that even the cumulative dose of 300 mgalphabisabolol/gmembrane administered through the skin would be safe to treat skin lesions.…”
Section: Alpha-bisabolol Release Kineticsmentioning
confidence: 99%
“…It has been widely used as an ingredient in dermatological and cosmetic formulations such as after shave creams, hand-and body-lotions, deodorants, lip sticks, sun-care and after-sun products, baby care products and sport creams [18]. It may be a preferred active ingredient for protection against the recurring stresses of the environment on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Bisabolol and bisabolol richoil have also demonstrated the capacity to enhance the percutaneous absorption of certain molecules and may prove to be an important ingredient for cosmetic and skin care products in the future [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Além de diminuir a produção de TNF- [36], também diminui a expressão da COX-2 [37]. α-(-)-Bisabolol, outro constituinte da Matricaria recutita, reduz a produção de citocinas pró-inflamatórias e diminui a inflamação da pele [38] promovida por diversos agentes [39].…”
Section: Avaliação Do Efeito Anti-inflamatóriounclassified